The innovation of sustainable business model in eco-edutourism: a way for creating society 5.0 - Kusdiyanti, Heny; Febrianto, Indra; Wijaya, Robby; Agustina, Nur Indah (BISMA (Bisnis dan Manajemen), 2022)
As a country with a huge population of more than 270 million people, Indonesia needs to reach society 5.0 to create a society-centred digital transformation. This study aims to formulate a business model for eco-edutourism in a vilage as a suburb with great potential in terms of natural resources and human resources. This research uses a qualitative approach with a type of case study. The primary and secondary data were obtained from semi-structured interviews, village databases, and related articles. The business model is formulated using the business model canvas with the identification of each element. The results show that the potential villages with natural resources and human resources can be developed into an education-based tourism village through its potential rich culture, cow farming, and proximity to another tourism destination. The business model canvas has been formulated from these potentials, which includes nine main elements. The main activities in this business are coffee processing educational tours, milk extracting educational tours, local cultural tours, nature tourism, and outbound tours. The value proposition formulated in the business model canvas in eco-edutourism is a social value that will focus on providing qualified education for visitors. The eco-edutourism initiation is expected to be an alternative to community-based digital transformation, especially in rural areas. Achieving digital transformation in the periphery areas on an ongoing basis can be a real step towards realising society 5.0 in Indonesia.